2002
DOI: 10.1097/01.asn.0000013297.11876.5b
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation Is Critical for the Plasma Membrane Localization of Nephrin

Abstract: Abstract. The expression pattern, subcellular localization, and the role of glycosylation of the human nephrin was examined in transfected cells. Stable cell lines, constitutively expressing a full-length human nephrin cDNA construct, were generated from transfected immortalized mouse podocytes (IMP) and a human embryonic kidney cell line (HEK-293). Immunofluorescence confocal microscopy of transfected cells showed plasma membrane localization of the recombinant nephrin. Immunoblotting showed that the recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 20 publications
4
97
0
1
Order By: Relevance
“…Thus MDCKnephrin cells provide a valuable alternative to working with isolated glomeruli or conditionally immortalized podocytes for investigating the interactions of nephrin. Immortalized podocytes have the limitation that nephrin expression is low 59 or ceases on extended passaging. 40 Furthermore, podocyte cell lines do not form continuous monolayers with distinct apical and basolateral domains.…”
Section: Discussionmentioning
confidence: 99%
“…Thus MDCKnephrin cells provide a valuable alternative to working with isolated glomeruli or conditionally immortalized podocytes for investigating the interactions of nephrin. Immortalized podocytes have the limitation that nephrin expression is low 59 or ceases on extended passaging. 40 Furthermore, podocyte cell lines do not form continuous monolayers with distinct apical and basolateral domains.…”
Section: Discussionmentioning
confidence: 99%
“…9,14,15 The following antibodies were purchased from the suppliers as indicated: anti-phospho-S6 ribosomal protein (S6RP) (Ser235/236) rabbit monoclonal, anti-S6RP rabbit monoclonal (5G10), anti-phospho-p70S6K (Thr389) rabbit polyclonal, anti-p70S6K rabbit polyclonal, anti-phospho-4EBP1 (ser65) rabbit polyclonal, anti-4EBP1 rabbit polyclonal, anti-phospho-AMP-activated protein kinase a (AMPKa) (Thr172) rabbit monoclonal, anti-AMPKa rabbit polyclonal, anti-phospho-a-subunit of eukaryotic translation initiation factor 2a (eIF2a) (Ser51) rabbit monoclonal and anti-eIF2a mouse monoclonal (L57A5) (Cell Signaling Technology, Beverly, MA, USA); anti-phospho-AKT1 (Ser473) rabbit polyclonal (Rockland, Gilbertsville, PA, USA); anti-glucose-regulated protein 78 mouse monoclonal (Stressgen Biotechnologies, Victoria, Canada); anti-b-actin mouse monoclonal (Sigma, Tokyo, Japan); HRPlabeled goat anti-rabbit and anti-mouse immunoglobulins (Dako, Carpinteria, CA, USA); and Alexa Fluor 488-conjugated goat anti-rabbit IgG, Texas Red-X goat anti-mouse IgG (Molecular Probes, Eugene, OR, USA). PAN was purchased from Sigma.…”
Section: Materials and Methods Antibodies And Reagentsmentioning
confidence: 99%
“…9 Nephrin is a transmembrane glycoprotein that is produced by podocytes and is responsible for the permselective barrier of the glomerulus. 12, 13 We previously determined that nephrin trafficking to the plasma membrane required N-glycosylation in the ER 14 and showed that a lack of ATP induced the hypoglycosylation of nephrin and its retention in the ER, which coincided with a strong induction of GRP78. 15 Interestingly, glucocorticoids and the immunosuppressant mizoribine, which are commonly used to treat MCD, normalized the abnormal N-glycosylation and nephrin localization by restoring ATP levels.…”
mentioning
confidence: 98%
“…Nephrin is a large (1241-amino acid, 185-kD) transmembrane molecule with Ig-like domains. N-linked glycosylation is critical for the plasma membrane localization of nephrin (66). Its predicted structure and biochemical properties, as well as electron microscopy studies, suggested that nephrin may form dimers through homophilic interactions across the filtration slit (67).…”
Section: The Critical Role Of Nephrin In Maintaining the Glomerular Fmentioning
confidence: 99%